Advertising, Attention, and Financial Markets - Florens Focke; Stefan Ruenzi; Michael Ungeheuer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We investigate the impact of product market advertising on investor attention and financial market outcomes. Using daily advertising data allows us to identify short-term effects of advertising. We measure daily investor attention based the company's number of Wikipedia page views. We show that TV and newspaper advertising positively impacts short-term investor attention. It also positively impacts turnover and liquidity, but the effects are not economically significant. Most importantly, asset prices are not influenced by advertising in the short run. These findings are different from studies using yearly advertising expenditures and suggest that attempts to temporarily inflate stock returns via short-term adjustments to advertising are ineffective.
Keywords: G10; G14; M37; 330